Evaluating the Impact of Sustainable Accounting Innovation on Economic Growth in Developing Countries - Ślusarczyk, Mikołaj; Górka, Zofia (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
This article explores the impact of sustainable accounting innovation on economic growth in Poland, focusing on the integration of environmental, social, and governance (ESG) factors into financial reporting. As Poland's economy transitions from heavy reliance on coal and traditional industries to more sustainable practices, adopting sustainable accounting becomes crucial for long-term growth and competitiveness. Sustainable accounting goes beyond traditional financial metrics to include ESG factors, allowing businesses to manage risks, attract investment, and improve transparency. The study examines the role of sustainable accounting in driving corporate responsibility, fostering investment, and improving operational efficiency in Poland. It highlights how businesses, particularly larger corporations, have started to integrate ESG factors into their financial reporting, but identifies significant challenges for small and medium-sized enterprises (SMEs), including limited awareness, lack of regulatory incentives, and the perceived high costs of implementation. The research also underscores the importance of standardized ESG reporting frameworks for improving the credibility and comparability of non-financial disclosures. While Poland has made strides in adopting EU regulations promoting sustainability, the widespread implementation of sustainable accounting practices is hindered by these challenges. The article concludes that by creating supportive policies, offering incentives for SMEs, and promoting standardized ESG reporting, Poland can fully leverage sustainable accounting to drive economic growth, attract responsible investment, and contribute to global sustainability goals.